Uso del método natural (Natural Approach) para la transmisión oral de la lengua Kichwa en niños de 0 a 3 años, Comunidad Cambugán - Iza, Nancy B. (2018)
The native people who were victims of various forms of oppression in colonial times, and exclusion in present times, have demonstrated their resistance to cultural characteristics, as in the case of language. However, in recent years the use of native languages has been decreasing, one of them the Kichwa, the ancestral language that manifests a decrease in its oral transmission to the new generations. In Ecuador there are 14 indigenous nationalities with a population of 1'018,176 and 13 languages, among them the Kichwa with a total of 591,448 Kichwa speakers, who at present this mother tongue is in a state of vulnerability due to the lack of intergenerational transmission.